The Soils of Iran (World Soils Book Series,, 2018)
This unique book addresses Iran's extremely rich soil diversity and resources, which have developed under various climatic conditions ranging from dry to humid conditions. Featuring contributions by a group of respected experts on Iranian soils and agriculture, it provides comprehensive information on the management approaches needed for sustainable soil utilization and conservation under such conditions, and the attendant challenges. As such, it offers a valuable resource for anyone interested in soils and agriculture in Iran, but also in other Middle East and North African countries with similar climatic conditions.